CHANGES IN SUSCEPTIBILITY TO VESICULAR STOMATITIS VIRUS DURING PROGRESSION OF PROSTATE CANCER - Yu, Nanmeng (Wake Forest University, 2013)
Vesicular stomatitis virus (VSV) is an attractive oncolytic virus. Differing sensitivity to VSV oncolysis of human prostate cancer cell lines has been observed in previous experiments. The goal of my experiments was to determine the mechanisms of sensitivity and resistance to VSV.